Bamboo Shoots Modulate Gut Microbiota, Eliminate Obesity in High-Fat-Diet-Fed Mice and Improve Lipid Metabolism - Xiaolu Zhou; SolJu Pak; Daotong Li; Li Dong; Fang Chen; Xiaosong Hu; Lingjun Ma (Foods, 2023)
Bamboo shoots (BS) have a variety of nutritional benefits; however, their anti-obesity effect and its underlying mechanism of action are still unclear. In this study, we investigated the protective effect of BS against high-fat diet (HFD)-induced gut dysbiosis in mice. After 12 weeks of feeding C57BL/6J mice either on a normal or an HFD with or without BS, metabolic indicators, including blood lipids and glucose tolerance, were measured. 16S rRNA gene sequencing and metabolomics were used to identify alterations in gut microbiota composition and fecal metabolic profiling. The results demonstrated that BS supplementation reduced body weight by 30.56%, mitigated liver damage, and improved insulin resistance and inflammation in obese mice. In addition, BS increased short-chain fatty acid (SCFA) levels and SCFA-producing bacteria (e.g., Lachnospiraceae_NK4A136_group and Norank_f_Muribaculaceae), and reduced levels of harmful bacteria (e.g., Blautia and Burkholderia–Paraburkholderia). Finally, BS increased many beneficial fecal metabolites, such as fatty acids and bile acids, which are highly relevant to the altered gut microbiota. Based on the modulatory effect of BS on microbiota composition and gut metabolite levels observed in this study, we suggest that BS may be beneficial in treating obesity and its related complications.